Optimization of Fly Ash and GGBS Proportions in Paving Blocks for Compressive and Flexural Strength Pavements - Biankalista, Intan Salma; Nabila, Nabila; Abdila, Syafiadi Rizki; Sumarno, Agung; Prasetyo, Agus Mudo; Budiman, Johan; Isradi, Muhammad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The increasing demand for environmentally friendly infrastructure has encouraged innovation in construction materials that can reduce carbon emissions. One of the efforts undertaken is the utilization of industrial by-products such as fly ash and Ground Granulated Blast Furnace Slag (GGBS) as partial substitutes for cement in the production of paving blocks. This study aims to investigate the effect of varying fly ash and GGBS mixtures on the compressive and flexural strength of paving blocks, as well as to determine the optimal mixture proportion that meets structural strength standards for pavement applications, particularly in heavy vehicle parking areas. The experimental method employed four mixture variations of fly ash and GGBS in a 1:1 ratio, namely 0%, 7.5%, 15%, and 25% of the cement weight. Compressive strength tests were conducted at curing ages of 7, 14, and 28 days, while flexural strength tests were performed at 28 days. The results showed that the mixture containing 85% cement, 7.5% fly ash, and 7.5% GGBS achieved the highest compressive and flexural strength values, 21.5 MPa and 4.3 MPa, respectively. These values meet the quality requirements of Grade B as specified in SNI 03-0691-1996, indicating that the paving blocks are suitable for use in heavy vehicle parking areas. The findings demonstrate that the appropriate incorporation of fly ash and GGBS not only enhances the mechanical performance of paving blocks but also contributes to reducing cement consumption and carbon emissions. Thus, this research provides a significant contribution to the development of more sustainable.